Effect of leaf ethyl acetate fraction Binahong (Anredera Cordifolia (Ten.) Steenis) on Uric Acid Levels of Hyperuricemia Male Mice - Hayati, Rahmi; Bimas Saputra, Ebit (Dinasti Health and Pharmacy Science, 2023)
A study on the effect of the ethyl acetate fraction of binahong leaves ( Anredera cordifolia (Ten.) Steenis) on uric acid levels in hyperuricemia male mice has been carried out. A total of 25 male mice were first induced with chicken liver juice 25 g/kg orally for 14 days to get hyperuricemia test animals. The test animals were divided into six groups, namely those that received 12.5 mg/kg, 25 mg/kg and 50 mg/kg fractions, positive control, negative control and 10 mg/kg allopurinol as a comparison. Data analysis used two-way analysis of variance (ANOVA) followed by Duncan's Multiple Range T-test with 95% confidence intervals. This study stated that the fraction used lowered blood uric acid levels. The best reducing effect of the fractions was shown by a dose of 50 mg/kg. This study shows that the ethyl acetate fraction of A. cordifolia exhibits antihyperuricemia activity which has the potential for drug development in the future.